Curves in multiplicative equiaffine plane - Ogrenmis, Meltem; Ogrenmis, Alper Osman; Mahmoud, Emad E. (De Gruyter Poland Sp Z O O, 2025)
In this study, we deal with multiplicative equiaffine plane curves. First, the concepts of multiplicative equiaffine arc length and multiplicative curvature are introduced. Multiplicative equiaffine Frenet formulas and an analog of the fundamental theorem are established. Finally, multiplicative equiaffine plane curves with constant multiplicative equiaffine curvature are classified.
Keywords: Affine plane; equiaffine plane curves; multiplicative derivative; multiplicative integral